2011
DOI: 10.1002/ajp.21002
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐specific patterns of vocal behavior in De Brazza's monkeys (Cercopithecus neglectus)

Abstract: Although vocal production is strongly genetically determined in nonhuman primates, vocal usage is more likely to be influenced by experience. Nonetheless, sex differences in both production and usage can be found in the vocal repertoire of adults, but little attention has been paid to their ontogeny. Here, we provide the first comprehensive analysis of the vocal repertoire of De Brazza's monkeys (Cercopithecus neglectus), with particular attention to age- and sex-specific patterns. This species has special int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Similar findings have already been reported in some species of Old World monkeys ( Cercocebus torquatus : Bouchet et al, 2010; C. neglectus : Bouchet et al, 2012), whereas a high degree of call type sharing between sexes is found in some other species, particularly macaques ( M. sylvanus : Hammerschmidt & Fischer, 1998; Macaca thibetana : Bernstein, Sheeran, Wagner, Li, & Koda, 2016). The great sex discrepancy in terms of call production in adult R. roxellana could be attributed to two non‐exclusive factors.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Similar findings have already been reported in some species of Old World monkeys ( Cercocebus torquatus : Bouchet et al, 2010; C. neglectus : Bouchet et al, 2012), whereas a high degree of call type sharing between sexes is found in some other species, particularly macaques ( M. sylvanus : Hammerschmidt & Fischer, 1998; Macaca thibetana : Bernstein, Sheeran, Wagner, Li, & Koda, 2016). The great sex discrepancy in terms of call production in adult R. roxellana could be attributed to two non‐exclusive factors.…”
Section: Discussionsupporting
confidence: 82%
“…For example, increasing the intensity of mounting grunts may lead to grunts , and further, if the duration increases and the f 0 decreases in grunts , long grunts may result. Although some primates have been considered to have graded vocal repertoires ( Macaca fuscata : Green, 1975; Macaca sylvanus : Hammerschmidt & Fischer, 1998) and some others have discrete vocal repertoires ( Cercopithecus diana : Zuberbühler, Noë, & Seyfarth, 1997; Cercopithecus neglectus : Bouchet et al, 2012), a mixed vocal system with both graded and discrete signals appears to be the norm for most primates, living in either relatively open or closed habitats (reviewed in Green & Marler, 1979; Papio hamadryas : Rendall, Notman, & Owren, 2009; Cercopithecus campbelli : Lemasson & Hausberger, 2011). The level of gradedness or discreteness is likely to be varied among different call types depending on their specific functions (Bouchet et al, 2013; Lemasson & Hausberger, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations